Carbapenem-resistant Klebsiella oxytoca transmission linked to preoperative shaving in emergency neurosurgery, tracked by rapid detection via chromogenic medium and whole genome sequencing - Jiang, Yun-Lan; Lyu, Yi-Yu; Liu, Li-Li; Li, Zhi-Ping; Liu, Dan; Tai, Jie-Hao; Hu, Xiao-Qian; Zhang, Wen-Hui; Chu, Wen-Wen; Zhao, Xue (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectivesThis study describes the detection and tracking of emergency neurosurgical cross-transmission infections with carbapenem-resistant Klebsiella oxytoca (CRKO).MethodsWe conducted an epidemiological investigation and a rapid screening of 66 surveillance samples using the chromogenic selective medium. Two CRKO isolates from infected patients and three from the preoperative shaving razors had similar resistance profiles identified by the clinical laboratory.ResultsThe whole genome sequencing (WGS) results identified all isolates as Klebsiella michiganensis (a species in the K. oxytoca complex) with sequence type 29 (ST29) and carrying resistance genes blaKPC-2 and blaOXY-5, as well as IncF plasmids. The pairwise average nucleotide identity values of 5 isolates ranged from 99.993% to 99.999%. Moreover, these isolates displayed a maximum genetic difference of 3 among 5,229 targets in the core genome multilocus sequence typing scheme, and the razors were confirmed as the contamination source. After the implementation of controls and standardized shaving procedures, no new CRKO infections occurred.ConclusionContaminated razors can be sources of neurosurgical site infections with CRKO, and standard shaving procedures need to be established. Chromogenic selective medium can help rapidly identify targeted pathogens, and WGS technologies are effective mean in tracking the transmission source in an epidemic or outbreak investigation. Our findings increase the understanding of microbial transmission in surgery to improve patient care quality.